Tantangan Socio-Cultural Bali Sebagai Daya Dukung Pariwisata Lombok - I Wayan Wirata (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
In preserving and preserving the culture and customs of Lombok culture, it is necessary to have a touch of understanding of regional culture. The existence of various studies and studies using methods and approaches, so that cultural preservation becomes a priority scale in the carrying capacity of Lombok tourism. The culture is expected to be maintained and preserved, because in it are stored noble values ​​inherited from their ancestors. These noble values ​​have a special attraction for others. This is seen from the aspect of form, facilities and other symbols, so that it can be used as a basis for the development of Lombok tourism. To increase the existence of Lombok tourism requires a strategy, in addition to the original packaging of regional culture. The existence of Sasak and Balinese culture which is part of local wisdom gives a significant style and color to the development of Lombok tourism, because it has long been acculturated in increasing the carrying capacity of tourism, especially in the field of hospitality. This study uses qualitative methods with data collection techniques of observation, in-depth interviews, and documentation. Analysis of the data used by interpretive techniques. The results of research on the challenges of socio-cultural Bali in Lombok tourism include arts such as welcoming dance (panyembrama dance, gabor, and pendet), places of worship, installation of mushrooms and banners at the time of important ivents in hotels. The hotel management has not permitted the tradition of Balinese Hindu symbols to be used in hotels, because they are considered to be in conflict with Islamic values. Besides in the field of culture, the phenomenon of local dances or art performances sometimes causes resistance such as the performances of the Panyembrama Dance, the Gabor Dance, the Puspanjali Dance in several areas of the Hotel Lombok.